The role of cyclosporin in the treatment of severe myasthenia: a clinical study of 51 patients - N. I. Shcherbakova; E. М. Pavlova; V. B. Lantsova; N. G. Savitskaya; E. V. Pavlov; I. G. Retinskaya; V. N. Zakutnaya (Анналы клинической и экспериментальной неврологии, 2017)
About 1520% of myasthenic patients are refractory to standardsteroid therapy. The present study was aimed at evaluation ofefficacy and analysis of the algorithm of use of a novel immunosuppressantof natural origin, cyclosporine A, in the treatment ofsevere refractory forms of myasthenia gravis. In this work, for thefirst time on a large group of myasthenic patients (51 patientswho became ill at 580 years of age), mechanisms of action ofcyclosporine (sandimmun orally 2.55 mg/kg) on main levels ofneuro-muscular junction were studied, and new confirmation ofselective immune-modulating activity of cyclosporine (withouttotal decrease of patients immune system) was presented. Highefficacy and good tolerability of the drug in different pathogenicsubtypes of myasthenia gravis were shown. Cyclosporin may berecommended in refractory steroid-dependent myasthenia, aswell as in cases of combination of myasthenia with thymoma,autoimmune disorders and immunodeficiency viral infections.